Remote Sensing in Mineral Exploration Case Histories - Allum, J. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1981)
Summary Situations are discussed in which remotesensing has helped in the exploration forsilver, fluorite, gold, bauxite, ilmenite,and nickel. It is shown that remote sens-ing can be a specific tool, in tropical rain-forest terrains, for the exploration fornickel-laterite deposits. It is also shownthat the combined use of an airbornegamma-ray survey with the interpretationof a satellite image is an effective methodof exploring for heavy-mineral sands.